ANALISIS KINERJA PELAYANAN UPT TERMINAL TAMBAK OSO WILANGON MENGGUNAKAN METODE COVERAGE RATIO - Ronaldi, Andri (Jurnal Akuntansi AKUNESA, 2014)
This research aim to measure how effective the performance of the Department of Transportation in the city of Surabaya Tambak Oso Wilangon Station Unit in serving passengers who will use the services of the Tambak Oso Wilangon station. This research use method coverage ratio, which is the method used to compare between potential and realization of an existing budget in 2011 and 2012. The data is taken from the primary data report Tambak Oso Wilangon Station Unit. The results showed an increase of 0.05% in 2011 which amounted to Rp 761,292,150.00 from Rp 760,886,830.00 of the total potential. And the result showed an increased of 3.68% in 2012 which amounted to Rp 788,887,633.00 from Rp 760,886,830.00 of the potential total potential budgeting.Keyword: Performance, Station, Retribution, Coverage Ratio